Áreas de influencia y competencia espacial de grandes superficies comerciales: una aproximación en el caso de Zaragoza - Díez Cornago, Carmen; Escalona Orcao, Ana Isabel (Geographicalia, 2016)
The aim of the article is the determination of market areas and spatial competition in the case of three shopping centres in the urban areas of Zaragoza. The research was conducted in several stages, including the application of a gravitational model and the survey to consumers, in order to establish market shares and to calculate the market penetration of each shopping center in each urban district or area. The results support tlie usefulness of the model in describing the market share of shopping centres with reasonable accuracy, and bring a better knowledge of the commercial geography in Zaragoza as well.
Keywords: market areas; spatial competition; shopping centres; gravitational models.